2019
DOI: 10.3390/nu12010071
|View full text |Cite
|
Sign up to set email alerts
|

Varied Pathways of Infant Gut-Associated Bifidobacterium to Assimilate Human Milk Oligosaccharides: Prevalence of the Gene Set and Its Correlation with Bifidobacteria-Rich Microbiota Formation

Abstract: The infant’s gut microbiome is generally rich in the Bifidobacterium genus. The mother’s milk contains natural prebiotics, called human milk oligosaccharides (HMOs), as the third most abundant solid component after lactose and lipids, and of the different gut microbes, infant gut-associated bifidobacteria are the most efficient in assimilating HMOs. Indeed, the fecal concentration of HMOs was found to be negatively correlated with the fecal abundance of Bifidobacterium in infants. Given these results, two HMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
221
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(231 citation statements)
references
References 91 publications
9
221
1
Order By: Relevance
“…These results indicate that the utilization of GNB/LNB was not prioritized by B. longum in the presence of many other sugars, such as Gal, GlcNAc, or lactose released from HMOs/mucin O-glycans under our experimental conditions. It should be noted that the growth ability on LNB was completely abrogated by the disruption of gltA (Supplementary Figure S1), which is well-conserved among the infant gut-associated Bifidobacterium [11,96]. (A,B) or spectinomycin (C-F) resistance gene on a plasmid (pBFS38 or pBFO2, respectively) [97] was used for monitoring the growth.…”
Section: Co-culture Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicate that the utilization of GNB/LNB was not prioritized by B. longum in the presence of many other sugars, such as Gal, GlcNAc, or lactose released from HMOs/mucin O-glycans under our experimental conditions. It should be noted that the growth ability on LNB was completely abrogated by the disruption of gltA (Supplementary Figure S1), which is well-conserved among the infant gut-associated Bifidobacterium [11,96]. (A,B) or spectinomycin (C-F) resistance gene on a plasmid (pBFS38 or pBFO2, respectively) [97] was used for monitoring the growth.…”
Section: Co-culture Experimentsmentioning
confidence: 99%
“…longum (B. longum), are frequently detected in the stool of breast-fed infants. Many studies [9][10][11][12][13][14][15][16][17][18][19] have indicated that the formation of a bifidus-flora in the gut of breast-fed infants can be attributed to human milk oligosaccharides (HMOs), which are the third most abundant solid component in breastmilk after lactose and lipids [20][21][22]. Mothers produce the energy-rich HMOs, even though HMOs have no direct nutritional value for infants, as HMOs are resistant to digestive enzymes secreted in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…present in the digestive tract of newborns and infants differ in their ability to use and/or digest HMOs. In comparison with Lactobacillus gasseri, Bifidobacterium infantis has an excellent ability to digest HMOs [91,92]. The genome of B. infantis encodes 24 different glycosidases, responsible for cleaving individual monosaccharide units from oligosaccharides, including 2α-sialidase and 5α-L-fucosidase ( Figure 2) [85,[91][92][93].…”
Section: Shaping Of Infant's Gut Microbiome By Dietary Hmosmentioning
confidence: 99%